2015
DOI: 10.18632/oncotarget.3860
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant over-expression of COX-1 intersects multiple pro-tumorigenic pathways in high-grade serous ovarian cancer

Abstract: Cyclooxygenase-1 (COX-1) is implicated in ovarian cancer. However, patterns of COX expression and function have been unclear and controversial. In this report, patterns of COX-1 and COX-2 gene expression were obtained from RNA-seq data through The Cancer Genome Atlas. Our analysis revealed markedly higher COX-1 mRNA expression than COX-2 in high-grade serous ovarian cancers (HGSOC) and higher COX-1 expression in HGSOC tumors than 10 other tumor types. High expression of COX-1 in HGSOC tumors was confirmed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 70 publications
1
35
0
2
Order By: Relevance
“…The interaction between fixed ratios of panobinostat and olaparib was measured with the Combination Index (CI) method [25]. Clonogenic assays were performed and quantified as described [26]. …”
Section: Methodsmentioning
confidence: 99%
“…The interaction between fixed ratios of panobinostat and olaparib was measured with the Combination Index (CI) method [25]. Clonogenic assays were performed and quantified as described [26]. …”
Section: Methodsmentioning
confidence: 99%
“…The aforementioned findings suggest that blueberry juice decreases the levels of COX-1 and COX-2, and inhibits the progression of OC. Furthermore, detecting the levels of COX-1 and COX-2 aid in the prediction of patients at risk for OC, as reported in previous studies (24,34). Blueberry juice therapy may therefore provide a non-pharmaceutical treatment for patients with OC.…”
Section: Discussionmentioning
confidence: 62%
“…Subsequent to the blueberry treatment, the volumes of OC in the 500 mg group significantly decreased by 40% compared with the group that received no Blueberry juice affects the mRNA levels of COX-1 and COX-2 of OC in the mouse model. The present study investigated the effect of blueberries on the mRNA levels of COX-1 and COX-2 of OC in a mouse model, which are biomarkers of OC (24,28). The mRNA levels of COX-1 and COX-2 of OC in the mice were the highest in the control group compared with those in the models treated with blueberry juice (P=0.006; Fig.…”
Section: Effects Of Blueberry On Tumor Volumementioning
confidence: 81%
See 1 more Smart Citation
“…They showed that SC-560 attenuates PG production and EOC growth by reducing cell proliferation and/or accelerating apoptosis. Wilson et al20 reported that stable knockdown of COX-1 in OVCAR-3 ovarian cancer cells reduced gene expression in multiple protumorigenic pathways.Upregulation of COX-2 contributes to tumor growth and invasion in EOC. Smith et al…”
mentioning
confidence: 99%